INTRODUCING THE INTELLIGIBILITY ISSUES IN EIL CONTEXTS BY USING YOUTUBE VIDEO CLIPS - Imelwaty, Sri; Kemal, Edwar; Suharni, Suharni; Perpisa, Lili (TELL - US JOURNAL, 2021)
Communication problems may occur in EIL contexts when English language users from different linguistic and cultural backgrounds conveying their messages. Being intelligible should not be seen as simple as pronunciation problems but it has other essential issues beyond it. To overcome such problem, there is a need for the English language learners to be aware of the intelligibility issues. This paper discusses the importance of introducing the intelligibility issues in EIL contexts for English language learners at secondary education in order to prepare them to communicate effectively with the diverse English language users around the world. The analytical scheme developed by Hu and McKay (2014) which defines the dimension of integrating multilingual and multicultural practices is adopted to select the YouTube video clips for the teaching materials. This practical guidance for introducing the intelligibility issues to the secondary school students could be employed by the English teachers to raise their students’ awareness toward the construct of intelligibility in EIL contexts.